2019
DOI: 10.1007/s00167-019-05356-y
|View full text |Cite
|
Sign up to set email alerts
|

UniCAP offers a long term treatment for middle-aged patients, who are not revised within the first 9 years

Abstract: PurposeThe aim of this study was to investigate the long‐term outcome of the unicompartmental knee resurfacing prosthesis (UniCAP) using clinical and radiographic assessments, and to evaluate the revision and survival rates. MethodsThis was a prospective cohort study of patients with UniCAP prostheses with 6–9 years of follow‐up. The clinical examination included the Knee Society Score (KSS) and Visual Analogue Scale (VAS) score. The radiographic examination included the Kellgren–Lawrence (KL) grading scale. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…This suggests that if symptomatic degenerative cartilage lesions are of limited size rather than an element of generalized OA, then resurfacing implant treatment can provide long-term improvement. The results of 70% not revised to knee arthroplasty after mean 9 years, indicate that resurfacing implants may limit the need for a UKA or TKA in elderly patients (> 65 years old) with symptomatic cartilage lesions or early degenerative knee pathologies [8,11,[15][16][17][18]. Thus far, the present study is the only and largest long-term case series, with 23 femoral resurfacing mini prostheses in elderly knee-patients with clinical and radiographic follow-up up to 11 years, including revision and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that if symptomatic degenerative cartilage lesions are of limited size rather than an element of generalized OA, then resurfacing implant treatment can provide long-term improvement. The results of 70% not revised to knee arthroplasty after mean 9 years, indicate that resurfacing implants may limit the need for a UKA or TKA in elderly patients (> 65 years old) with symptomatic cartilage lesions or early degenerative knee pathologies [8,11,[15][16][17][18]. Thus far, the present study is the only and largest long-term case series, with 23 femoral resurfacing mini prostheses in elderly knee-patients with clinical and radiographic follow-up up to 11 years, including revision and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“… 64 Long-term follow-up of FKRIs is scarce, and available long-term evidence from the first-generation metal FKRI raised concerns because of high failure rates based on OA progression. 46 Novel metal FKRIs with patient-specific surface geometries have resulted in very low failure rates up to 55 months. 38 , 55 Cartilage-mimicking polymers, such as in the study by Nathwani et al, 64 pose great potential for prevention of OA progression when using FKRIs.…”
Section: Discussionmentioning
confidence: 99%
“…There were 12 conversions to arthroplasty in patients aged 50 years versus 1 patient in the <50 years subgroup. Finally, Gille et al 28 compared 3 age groups (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), and 47-65 years) after AMIC cartilage repair and found no significant differences in outcome across all age groups.…”
Section: Bone Marrow Stimulationmentioning
confidence: 99%
“…22 Studying the HemiCap Wave for patellofemoral defects, the authors found a revision rate of 28% after 6 years in 18 patients 22 and in 64 patients treated with UniCap (designed for larger defects), the authors found a revision rate of 56%. 23 Laursen et al . 22 reported that the subgroup of patients who did not require early revision had lasting clinical improvements, and no progression of osteoarthritis was seen, while patients suffering from osteoarthritis and patients who did hard, manual labor had a significantly higher risk of revision.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies report a relatively high revision rate. 22-24 Therefore, our objective was to investigate the 10-year survival of resurfacing implants from a nationwide cohort registered in the Danish Knee Arthroplasty Registry.…”
Section: Introductionmentioning
confidence: 99%